Inhibitory effect of licorice extract on the germination and outgrowth of Paraclostridium bifermentans spores - Song, Mengmeng; Lei, Yang; Ali, Ahtisham; Xu, Yan; Sheng, Kairan; Huang, Tianran; Huang, Jichao; Huang, Ming (Frontiers in Microbiology, 2022)
Introduction Paraclostridium bifermentans is responsible for spoilage properties in vacuum-packaged meat. Ordinary heat treatment techniques are ineffective to control the extremely heat-resistant spores of P. bifermentans. Therefore, finding a new strategy to prevent the contamination of P. bifermentans spores in vacuum-packaged meat is challenging. Methods In this study, P. bifermentans was isolated from the vacuum-packaged chicken, and the inhibitory effects of licorice extract on the germination and outgrowth of P. bifermentans spores, as well as the key bioactive components in the licorice extract involved in inhibiting spore activity, were investigated. Results The spores induced by combination-nutrient-germinant (150 mmol/L L-alanine and 20 mmol/L inosine, co-AI) did not germinate when the concentration of licorice extract was ≥ 3.13 mg/ml. The germination of P. bifermentans spores induced by non-nutrient-germinant (8 mmol/L dipicolinic acid, DPA) was completely prevented by licorice extract at least 1.56 mg/ml. While the outgrowth of P. bifermentans spores was inhibited at a concentration of 0.39 mg/ml. Licorice extract did not seem to damage the non-germinated spores but blocked the germinant sensing. Licorice extract prevented the outgrowing spores from becoming vegetable cells by disrupting the inner membrane. Furthermore, the results obtained from LC-MS data analysis exhibited 15 key bioactive compounds in licorice extract, such as glycyrrhizic acid, liquiritin, etc. Among them, glycyrrhizic acid and liquiritin apioside exerted efficient inhibitory properties on the germination and outgrowth of P. bifermentans spores. Discussion This present study demonstrated that licorice extract can be used as a promising inhibitor of spores and provides a new method to control the residual P. bifermentans spores in meat products. Meanwhile, this study exhibits a baseline for the better understanding of the potential application of licorice extracts to control the P. bifermentans spores in meat products.